Effect of NiO doping on grain growth and electrical properties of ZnO-based varistors. Issue 9 (August 2022) - Jiang, Haibo; Ren, Xin; Lao, Xuebin; Kong, Anting; Zhong, Meilian; Sun, Yan; Wu, Yucong; Yao, Zheng; Shi, Liyi
Abstract: The effects of NiO content on the grain growth and the electrical properties of the ZnO varistors were studied. The effect on the grain growth was characterized by scanning electron microscopy, energy dispersive spectroscopy and X-ray diffractometer, while the effects on the electrical properties were investigated by varistor tester, pulse surge tester and precision impedance analyzer. The results showed that the growth of the (0002) plane of the ZnO varistors was inhibited by doping NiO, which improved the electrical properties of the varistors, especially the surge shock stability. The sample doped with 1.56 mol% NiO exhibited excellent electrical properties with breakdown voltage gradient of 184.0 V/mm, nonlinear coefficient of 72.7, leakage current of 0.37 µA, clamp voltage ratio of 2.20 under 8/20 μs waveform impact of 20 kA and change rates of positive and negative breakdown voltages of < 4% under 20 times impacts of 20 kA.